2013
DOI: 10.2178/jsl.7804130
|View full text |Cite
|
Sign up to set email alerts
|

A Perfect Set of Reals with Finite Self-Information

Abstract: We examine a definition of the mutual information of two reals proposed by Levin in [5]. The mutual information is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…If A is also ∆ 0 2 , it is therefore low, in the usual computability theoretic sense. However, Herbert [8] has recently shown that there is a perfect Π 0 1 class of sets that have finite self-information, which in particular answers a question in a previous version of this paper by showing the existence of non-∆ 0 2 sets with finite self-information. Lutz [16] and others have developed an effective version of Hausdorff dimension based on martingales in inflationary environments, called s-gales.…”
Section: Relationships To Other Weakness Notionssupporting
confidence: 66%
See 1 more Smart Citation
“…If A is also ∆ 0 2 , it is therefore low, in the usual computability theoretic sense. However, Herbert [8] has recently shown that there is a perfect Π 0 1 class of sets that have finite self-information, which in particular answers a question in a previous version of this paper by showing the existence of non-∆ 0 2 sets with finite self-information. Lutz [16] and others have developed an effective version of Hausdorff dimension based on martingales in inflationary environments, called s-gales.…”
Section: Relationships To Other Weakness Notionssupporting
confidence: 66%
“…In the forthcoming paper [11], Lempp, Miller, Ng, Turetsky, and Weber show that there is in fact a perfect Π 0 1 class of sets that are low for effective Hausdorff dimension, a result that also follows by the methods of Herbert [8].…”
Section: Relationships To Other Weakness Notionsmentioning
confidence: 91%
“…In this section, we prove the latter fact by constructing a perfect Π 0 1 -class containing only lowish for K sequences. This result was also recently proved by Herbert [9]. He built a perfect Π 0 1 -class Q ⊆ 2 ω of sequences with finite self-information (see Section 7) and observed that, as a consequence of his construction, every element of Q is low for dimension.…”
Section: A Perfect Class Of Low For Dimension Setsmentioning
confidence: 58%
“…They observed that their sequence is also low for dimension, so lowness for dimension does not imply lowness for randomness. We can also see this as a corollary to Theorem 5.1, where we prove that there are continuum many sequences that are low for dimension (see also Herbert [9]). Chaitin [4] proved that every K-trivial is ∆ 0 2 , so there are only countably many low for random sequences.…”
mentioning
confidence: 56%
“…Another closure property we get for KT p∆ 0 2 q, in contrast to LKp∆ 0 2 q as in [8], is that KT p∆ 0 2 q is closed under effective join (the effective join of reals A and B, denoted A' B, is the real whose binary expansion is given by A' Bp2nq " Apnq and A ' Bp2n`1q " Bpnq). The proof follows closely the proof that KT p0q is closed under effective join that was given by Downey, Hirschfeldt, Nies, and Stephan [7].…”
Section: Other Closuresmentioning
confidence: 95%